American government : - Lowi, Theodore J. (W. W. Norton & Company, 2008)
American Government, Brief Tenth Edition, is the only brief text that offers an analytical approach, comprehensive coverage of the core concepts and major topics of American politics, and lots of pedagogical help for students.